Micronutrient intake adequacy in children from birth to 8 years. Data from the Childhood Obesity Project. Issue 2 (April 2018) - Zaragoza-Jordana, Marta; Closa-Monasterolo, Ricardo; Luque, Veronica; Ferré, Natàlia; Grote, Veit; Koletzko, Berthold; Pawellek, Ingrid; Verduci, Elvira; ReDionigi, Alice; Socha, Jerzy; Stolarczyk, Anna; Poncelet, Pascale; et al.
Summary: Background: In European countries, suboptimal intake has been reported for several micronutrients (as calcium, iron, zinc, vitamin B12, D and folate) in both adulthood and childhood. No studies to date have prospectively compiled nutrient intake from healthy children in different European countries using the same methodology. Aim: To describe the adequacy of micronutrient intake during the first eight years of life in children from 5 European countries. Methods: Prospective observational trial analyzing data from the EU Childhood Obesity Project. Infants were enrolled within the first two months of life and were followed regularly to age 8 years. Dietary intake was collected periodically with 3-day food records. Nutrient intake adequacy was estimated for calcium, phosphorus, iron, zinc, magnesium, iodine, folate and vitamins B12, A and D, following the American Institute of Medicine (IOM) guidelines at group (prevalence of adequacy >80%) and individual (high probability of adequate intake >80% of the children) level; the assessment was based on the Estimated Average Requirements of nutrients of the FAO, WHO and United Nations University (FAO/WHO/UNU) or the IOM if FAO/WHO/UNU data were not available. Results: Intake data were available for a decreasing number of children, from 904 at 3 months to 396 at 8 years. Iron, iodine, folate and vitamin D were inadequately consumed when assessing adequacy at group level; at individual-level less than 80% of the children showed high probability of adequate intake for iron, iodine, folate and zinc at all ages, and calcium from 12 months onwards. Conclusions: Accurate dietary intake and adequacy assessment methodology in this prospective cohort of European children found iron, calcium, vitamin D, folate, iodine and zinc to be inadequately consumed in childhood, as described previously by epidemiologic studies. Further studies are needed to elucidate health consequences of these deficiencies. CHOP trial was registered at clinicaltrials.gov asNCT00338689 .